Fintech Disruption and Operational Risk in the Banking Sector: Evidence from a Systematic Literature Review - Tarada Berlian Megananda; Sulwani Husna Afrizal (International Journal of Management and Business Economics, 2025)
The rapid advancement of financial technology (fintech) has significantly disrupted the traditional banking sector by introducing innovative services and business models that enhance efficiency, reduce costs, and promote financial inclusion. However, these benefits also bring emerging operational risks, such as cybersecurity threats, data privacy concerns, and regulatory compliance challenges. This systematic literature review synthesizes findings from 13 peer-reviewed journal articles published in the last five years, selected through a rigorous PRISMA-based methodology. The analysis identifies key themes, including the transformative role of technologies like artificial intelligence, blockchain, and big data analytics; the reconfiguration of risk management frameworks; and the evolving relationship between digital innovation and operational resilience. The results indicate that while fintech adoption offers substantial opportunities for competitiveness and customer engagement, it also necessitates proactive governance, robust cybersecurity measures, and continuous workforce upskilling. The discussion emphasizes the need for collaborative efforts among regulators, financial institutions, and technology providers to develop adaptive strategies that can mitigate risks in an evolving digital landscape. By addressing both the opportunities and vulnerabilities presented by fintech disruption, this review enhances our understanding of its implications for operational risk in banking and provides directions for future research.